2019
DOI: 10.17159/2309-8309/2019/v18n4a1
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of elbow functional outcome after closed reduction and percutaneous pinning of displaced supracondylar humerus fractures in children

Abstract: Background: The aim of the current study was to establish the functional outcome of Gartland grade III extension-type supracondylar fractures at 24 weeks after closed reduction and percutaneous pinning (CRPP) without physiotherapy. The objectives of this study were 1) to measure the elbow range of motion (ROM) at three, six, 12 and 24 weeks after CRPP for grade III supracondylar fractures; 2) to assess the functional outcome of the injured limb using the Paediatric Outcome Data Collection Instrument (PODCI) sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…[16][17][18][19][20][21] In all such papers, the average pin removal date was never longer than 28 days postoperatively in any group, and therefore despite a lack of robust literature evidence, this appears to be a widely used time period. Rutarama et al 22 showed good functional outcomes in a prospective cohort of 38 children with Gartland type III supracondylar fractures who were all immobilized for 3 weeks post reduction and K-wires, but there was no comparator group.…”
Section: Discussionmentioning
confidence: 99%
“…[16][17][18][19][20][21] In all such papers, the average pin removal date was never longer than 28 days postoperatively in any group, and therefore despite a lack of robust literature evidence, this appears to be a widely used time period. Rutarama et al 22 showed good functional outcomes in a prospective cohort of 38 children with Gartland type III supracondylar fractures who were all immobilized for 3 weeks post reduction and K-wires, but there was no comparator group.…”
Section: Discussionmentioning
confidence: 99%